Quasi-Axisymmetric Finite-Difference Method for Realistic Modeling of Regional and Global Seismic Wavefield — Review and Application — - Toyokuni, Genti; Takenaka, Hiroshi; Kanao, Masaki (IntechOpen, 2012)
None